Upaya Meningkatkan Produktivitas Petani Dengan Mengurangi Nyeri Pada Kasus Low Back Pain Di Desa Jaten - Arif Pristianto; Milan Dwi Winanti; Muhammad Rais Hasan Firdaus; Hasan Mujaddid; Muhammad Isa Hanafi; Qoriah Titin Masyitoh (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is an agricultural country where the majority of the population work as farmers. The work that farmers do every day is very draining. When working, farmers tend to use more lumbar flexion movements and do them continuously or repetitively. According to research, the working position of farmers has the highest risk, reaching 87.4% with pain complaints of 93.7%. This condition often causes complaints of low back pain or Low Back Pain. Back pain affects the decrease in muscle strength so that it will reduce farmer productivity. The main problem for farmers in Jaten Village is complaints of pain during the planting and harvesting periods, which requires a lot of energy but is hampered by disturbing lower back pain. One solution for farmers in Jaten Village is to be given education on how to reduce pain by counseling farmers about Mc. Kenzie and William Flexion Exercise and education on posture and stretching on the lumbar. Based on the problems we found in the farming community at GAPOKTAN, we carried out community service in the form of counseling related to efforts to increase the work productivity of farmers by reducing pain in the case of Low Back Pain. The method used is counseling with material presentations and distributing leaflets to members of the farming community. From the results of the evaluation data with the pre-test and post- test there was a significant increase from 28.4% to 92%.